High power density inverter utilizing SiC MOSFET and interstitial via hole PCB for motor drive system. Issue 2 (14th February 2021) - Sato, Ikuya; Tanaka, Takaaki; Hori, Motohito; Yamada, Ryuuji; Toba, Akio; Kubota, Hisao
Abstract: This paper proposes a high power density inverter utilizing SiC metal‐oxide‐semiconductor field‐effect transistor (MOSFET) modules and an interstitial via hole (IVH) printed circuit board (PCB) for a motor drive system. The inverter also includes a power circuit, heatsink, cooling fan, gate drive circuit, and DC capacitors. The output power density of the proposed inverter is 81 kW/L. The inverter outputs 37 kW for motor drive applications. To achieve this superior output power density, this paper explains a prototype SiC MOSFET module without an antiparallel schottky barrier diode, and a unique multilayer laminate IVH PCB to connect the modules and DC capacitors. This paper describes the experimental results to verify the motor drive performance and the increase in temperature under the rated load operation.